1992
DOI: 10.1021/ie00011a009
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methane from compressed natural gas fueled vehicle exhaust

Abstract: The objective of this study is to investigate the modes of methane (CH$ removal from simulated compressed natural gas (CNG) fueled vehicle exhaust under net oxidizing, net reducing, and stoichiometric conditions. Model reaction studies were conducted. The results suggest that the oxidation of methane with oxygen contributes to the removal of methane under net oxidizing conditions. In contrast, the oxidation of methane with oxygen as well as nitric oxide contributes to ita removal under net reducing conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Subramanian and coworkers extensively investigated model reactions (CH 4 -NO-CO-H 2 -O 2 , CH 4 -NO-CO-O 2 , CH 4 -O 2 , CH 4 -NO, etc.) over 1 % Pd/Al 2 O 3 with different feedstream compositions, from reducing to stoichiometric to oxidizing atmospheres [16]. However, the temperature examined in their study was limited to 550°C, and activity at lower temperatures was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Subramanian and coworkers extensively investigated model reactions (CH 4 -NO-CO-H 2 -O 2 , CH 4 -NO-CO-O 2 , CH 4 -O 2 , CH 4 -NO, etc.) over 1 % Pd/Al 2 O 3 with different feedstream compositions, from reducing to stoichiometric to oxidizing atmospheres [16]. However, the temperature examined in their study was limited to 550°C, and activity at lower temperatures was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Subramanian et al [17] reported high conversion efficiencies for Pd-based catalysts, and recent systematic studies of silica or alumina supported Pd, Pt and Rh catalysts have been reported by Burch et al [18,19]. Measurements were made both in the absence and in the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the addition of ceria is to stabilize PdO [11] thus avoiding large activity losses after exposure to high temperatures, especially under oscillating red-ox conditions. Additionally, there is also indication that the complex chemistry involved in the operation of TWC maybe different between natural gas and gasoline engines and other reactions (than CH 4 oxidation) alone can contribute to CH 4 removal from the exhaust [12,13]. Therefore, it is of interest to investigate CH 4 oxidation over Pd-based catalysts under simulated exhaust of stoichiometric natural gas engines [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%